2023
DOI: 10.1029/2023ja031947
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Blanketing Sporadic‐E Layer and Associated Tidal Periodicities Over a Brazilian Station Undergoing a Transition From Low Latitude to Midlatitude

J. Moro,
J. Xu,
J. V. Bageston
et al.

Abstract: Analyses on a complete year of Digisonde data are conducted to investigate the sporadic‐E (Es) layers over Santa Maria (29.7°S, 53.8°W, dip lat.: −37°), Brazil. This region is undergoing a transition from low latitude to midlatitude within the South American Magnetic Anomaly (SAMA), which provides a key motivation to explore their behavior and the associated tidal periodicities. The Es are classified into four types: flat (Esf), low (Esl), high (Esh), and cusp (Esc). The diurnal and seasonal variations of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Mid-latitude Es layer is a prominent phenomenon in the atmosphere-ionosphere coupling system because its formation process is generally controlled by the interaction between neutral wind shears and metallic ions acting in the presence of the Earth's magnetic field (Haldoupis, 2011;Whitehead, 1989). Observations and simulations have confirmed that the Es layer occurrence has significant diurnal and semidiurnal behaviors associated with atmospheric tides (Andoh et al, 2022;Moro et al, 2023;Qiu et al, 2023b;Sobhkhiz-Miandehi et al, 2022;Yamazaki et al, 2021;Yu et al, 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Mid-latitude Es layer is a prominent phenomenon in the atmosphere-ionosphere coupling system because its formation process is generally controlled by the interaction between neutral wind shears and metallic ions acting in the presence of the Earth's magnetic field (Haldoupis, 2011;Whitehead, 1989). Observations and simulations have confirmed that the Es layer occurrence has significant diurnal and semidiurnal behaviors associated with atmospheric tides (Andoh et al, 2022;Moro et al, 2023;Qiu et al, 2023b;Sobhkhiz-Miandehi et al, 2022;Yamazaki et al, 2021;Yu et al, 2023).…”
Section: Introductionmentioning
confidence: 97%